PERBEDAAN FUNGSI KELUARGA DAN KUALITAS HIDUP ISTRI ANTARA ISTRI BEKERJA DAN TIDAK BEKERJA - Candrasari, Anika; Probandari, Ari Natalia (Universitas Muhamadiyah Surakarta, 2013)
Along economic progress and increase in women education, so many housewives today serve not only as manager of their household, but also work outside home. It will have various social implications, such as stress due to work overloads, increased teenage delinquency due to lack of parental attention, lack of marriage or family values. This study aimed to analyze the differences of family function and wifeâs quality of life among wife with and without occupation. Location of study was Bolon village, District Colomadu, Karanganya, Central Java. The study used an observational analytic design, with a cross-sectional approach. The study population was wives. Sampling used 128 wives. The instruments were APGAR, SCREEM family function and WHOQOL. From t test, it showed signifi cant differences family function and wifeâs quality of life among wife with and without occupation (APGAR p = 0.023, SCREEM p = 0.001 and wifeâs quality of life p = 0.043).Keywords: family function, quality of life, wife, work.